Seasonal variation in wing geometry of the malaria vector Anopheles maculatus (Diptera: Culicidae) in Western Thailand - Sumruayphol, Suchada; Chaiphongpachara, Tanawat; Laojun, Sedthapong (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: Anopheles maculatus is recognized as an important malaria vector in Thailand and other countries within the Greater Mekong Subregion. This study employed both landmark and outline-based geometric morphometrics (GM) approaches to assess seasonal variation in the wing structure and wing contour of A. maculatus from malaria hotspots in western Thailand across three seasons: hot, wet, and dry. Materials and Methods: We analyzed seasonal variation in wing structure and contour using landmark-based and outline-based GM approaches, respectively, applied to the same image set of wing samples. Statistical differences in size and shape among seasonal populations were evaluated using a non-parametric analysis of variance (1,000 replicates), followed by a Bonferroni post hoc test. A p-value of less than 0.05 was used as the criterion for statistical significance in all analyses. Results: The size analyses revealed a significant difference in wing structure between the hot and dry seasons (p < 0.05), while no significant differences (p > 0.05) in wing contour across seasonal populations were detected. Significant differences (p < 0.05) in wing structure based on shape were detected between A. maculatus populations in the dry and hot seasons, as well as between populations in the dry and wet seasons. Wing contour analysis based on shape showed a significant difference (p < 0.05) only between the populations from the dry and wet seasons. Conclusion: These findings provide us with valuable information about the seasonal adaptation of A. maculatus, thus enhancing our understanding of vector population dynamics and potentially improving malaria surveillance strategies. J. Adv. Vet. Anim. Res., 12(3): 870–880, September 2025 http://doi.org/10.5455/javar.2025.l949